Decreased vaccine protection of egg-based influenza vaccine in the elderly and nonhemagglutinin-focused immunity - Karen J. Gonzalez; Eva M. Strauch (The Journal of Clinical Investigation, 2021)
Severe influenza illness or death is a serious concern among the elderly population despite vaccination. To investigate how the adaptive immune response after vaccination varies with the patient’s age, Jung et al., in a recent issue of the JCI, extensively analyzed the serum antibody response in different age groups after immunization with the egg-based influenza vaccine Fluzone. As expected, the immune response in young adults was dominated by antibodies targeting the influenza hemagglutinin (HA) protein. On the contrary, the serological repertoire of elderly donors was characterized by cross-reactive (CR) antibodies recognizing non-HA antigens. Surprisingly, a substantial fraction of these CR antibodies targeted sulfated glycans typical of egg-produced proteins, which does not provide protection against human influenza viruses. Overall, these findings are of great value in understanding suboptimal immunity after influenza vaccination and shaping future vaccine efforts that will achieve increased protection in the elderly.